The Generalization of the Classical Weighted Pseudo-Almost Periodic Solutions Under the Measure Theory to some Classes of Nonautonomous Partial Evolution Equations (Journal of Partial Differential Equations, 2018)
In this paper, we use a recentworks [9], where the authors provide a newapproach for pseudo almost periodic solution under themeasure theory, under Acquistpace-Terreni conditions, we make extensive use of interpolation spaces and exponential dichotomy techniques to obtain the existence of μ-pseudo almost periodic solutions to some classes of nonautonomous partial evolution equations.
Keywords: evolution family; exponential dichotomy; Acquistapace and Terreni conditions; almost periodic; pseudo almost periodic under the light measure; evolution equation; nonautonomous equation.